The enteropathogenic Escherichia coli effector NleH inhibits apoptosis induced by Clostridium difficile toxin B - Robinson, Keith S. (Microbiology Society, 2010)
Clostridium difficile is a leading cause of nosocomial infections, causing a spectrum of diseases ranging from diarrhoea to pseudomembranous colitis triggered by a range of virulence factors including C. difficile toxins A (TcdA) and B (TcdB). TcdA and TcdB are monoglucosyltransferases that irreversibly glycosylate small Rho GTPases, inhibiting their ability to interact with their effectors, guanine nucleotide exchange factors, and membrane partners, leading to disruption of downstream signalling pathways and cell death. In addition, TcdB targets the mitochondria, inducing the intrinsic apoptotic pathway resulting in TcdB-mediated apoptosis. Modulation of apoptosis is a common strategy used by infectious agents. Recently, we have shown that the enteropathogenic Escherichia coli (EPEC) type III secretion system effector NleH has a broad-range anti-apoptotic activity. In this study we examined the effects of NleH on cells challenged with TcdB. During infection with wild-type EPEC, NleH inhibited TcdB-induced apoptosis at both low and high toxin concentrations. Transfected nleH1 alone was sufficient to block TcdB-induced cell rounding, nuclear condensation, mitochondrial swelling and lysis, and activation of caspase-3. These results show that NleH acts via a global anti-apoptotic pathway.